Bringing Light to Transcription: The Optogenetics Repertoire - de Mena, Lorena; Rizk, Patrick; Rincon-Limas, Diego E. (Frontiers in Genetics, 2018)
The ability to manipulate expression of exogenous genes in particular regions of living organisms has profoundly transformed the way we study biomolecular processes involved in both normal development and disease. Unfortunately, most of the classical inducible systems lack fine spatial and temporal accuracy, thereby limiting the study of molecular events that strongly depend on time, duration of activation, or cellular localization. By exploiting genetically engineered photo sensing proteins that respond to specific wavelengths, we can now provide acute control of numerous molecular activities with unprecedented precision. In this review, we present a comprehensive breakdown of all of the current optogenetic systems adapted to regulate gene expression in both unicellular and multi cellular organisms. We focus on the advantages and disadvantages of these different tools and discuss current and future challenges in the successful translation to more complex organisms.